(untitled) (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: Increasing Economic Learning Outcomes Through Problem Based Learning Learning Models. This study aims to determine the process of economic learning in SMA Negeri 13 with Problem Based Learning (PBL) learning models, it can increase the activeness of students so that they can improve the learning outcomes of economics for students of class X.IPS.2 Palembang State High School 13. The research used was Classroom Action Research (CAR) or Classroom Action Research (CAR). In this study there are several cycles. Each cycle consists of 4 stages of interrelated and continuous activities, namely: planning, acting, observing and reflecting. The subjects referred to actions in this study were students of class X IPS. 2 Palembang 13 State Senior High Schools totaling 40 students. Data collection techniques use tests and observations. The results of this study indicate that by applying the Problem Based Learning (PBL) learning model the learning outcomes of students can be seen from the results before the action is taken and after the action is taken, namely; cycle I (65%), and cycle II (92.50%). Means there is an increase in student learning outcomes and learning process activities of students after class action research. Keywords: Economy, Problem Based Learning Abstrak: Meningkatkan Hasil Belajar Ekonomi Melalui Model Pembelajaran Problem Based Learning . Penelitian ini bertujuan untuk mengetahui proses pembelajaran ekonomi di SMA Negeri 13 Palembang dengan model pembelajaran Problem Based Learning (PBL), dapat meningkatkan keaktifan peserta didik sehingga dapat meningkatkan hasil belajar ekonomi pada peserta didik kelas X.IPS.2 SMA Negeri 13 Palembang. Penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) atau Classroom Action Research (CAR). Dalam penelitian ini terdapat beberapa siklus. Setiap siklus terdiri atas 4 tahap kegiatan yang saling terkait dan berkesinambungan yaitu: perencanaan tindakan (planning), pelaksanaan tindakan (acting), pengamatan (observing) dan refleksi (reflecting). Subjek yang dimaksud tindakan dalams penelitian ini adalah peserta didik kelas X IPS.2 SMA Negeri 13 Palembang yang berjumlah 40 peserta didik. Teknik pengumpulan data menggunakan tes dan observasi. Hasil penelitian ini menunjukkan dengan menerapkan model pembelajaran Problem Based Learning (PBL) hasil belajar peserta didik meningkat dapat dilihat dari hasil sebelum dilakukan tindakan dan sesudah dilakukan tindakan yaitu; siklus I (65%), dan siklus II (92.50%). Berarti terdapat peningkatan hasil belajar peserta didik dan aktivitas proses pembelajaran para peserta didik setelah dilakukan penelitian tindakan kelas. Kata Kunci : Ekonomi, Problem Based Learning